Potential Use of Human Periapical Cyst-Mesenchymal Stem Cells (hPCy-MSCs) as a Novel Stem Cell Source for Regenerative Medicine Applications - Tatullo, Marco; Codispoti, Bruna; Pacifici, Andrea; Palmieri, Francesca; Marrelli, Massimo; Pacifici, Luciano; Paduano, Francesco (Frontiers in Cell and Developmental Biology, 2017)
Mesenchymal stem cells (MSCs) are attracting growing interest by the scientific community due to their huge regenerative potential. Thus, the plasticity of MSCs strongly suggests the utilization of these cells for regenerative medicine applications. The main issue about the clinical use of MSCs is related to the complex way to obtain them from healthy tissues; this topic has encouraged scientists to search for novel and more advantageous sources of these cells in easily accessible tissues. The oral cavity hosts several cell populations expressing mesenchymal stem cell like-features, furthermore, the access to oral and dental tissues is simple and isolation of cells is very efficient. Thus, oral-derived stem cells are highly attractive for clinical purposes. In this context, human periapical cysts mesenchymal stem cells (hPCy-MSCs) exhibit characteristics similar to other dental-derived MSCs, including their extensive proliferative potential, cell surface marker profile and the ability to differentiate into various cell types such as osteoblasts, adipocytes and neurons. Importantly, hPCy-MSCs are easily collected from the surgically removed periapical cysts; this reusing of biological waste guarantees a smart source of stem cells without any impact on the surrounding healthy tissues. In this review, we report the most interesting research topics related to hPCy-MSCs with a newsworthy discussion about the future insights. This newly discovered cell population exhibits interesting and valuable potentialities that could be of high impact in the future regenerative medicine applications.